INVESTIGATION OF THE COMPOSITION OF POLYPHENOLIC SUBSTANCES OF THE JUICE FROM ARTICHOKE TUBERS - Z. Tuleshova; G.I. Baigazieva; E. Askarbekov (Academic Scientific Journal of Chemistry, 2021)
Currently, the growth of diseases with diabetes, metabolic disorders, and obesity increases the demand for preventive and functional products. Currently available technologies for the production of preventive products provide for the replacement of sugar with sugar substitutes or its complete absence, which naturally reduces the nutritional and energy value of the products produced. One of the main promising areas of the processing industry is the production of new products and sugar substitutes based on non-traditional types of plant raw materials that have a rich carbohydrate complex in their composition. These types of raw materials among vegetable crops include jerusalem artichoke. Currently, jerusalem artichoke juice is of particular interest for use in the production of soft drinks, as it has a rich chemical composition, which makes Jerusalem artichoke indispensable in dietary nutrition, in the preparation of highly effective medicines. In this article, the chemical composition of tubers and juice-semi-finished products from jerusalem artichoke is investigated. The results of the studies showed that the bulk of the dry substances in jerusalem artichoke tubers are carbohydrates, most of which are represented by fructosides. In the semi-finished juice passes: oligosaccharides 22.54 %, monosaccharides 1.61%, as well as part of the structural polysaccharides-fiber 0.07 %, pectin substances 1.84 %. The change in the fractional composition of the polyphenolic substances of the pulp and semi - finished juice was studied when the pulp was kept for 30 minutes. When developing the technology for the production of juices and beverages based on jerusalem artichoke, it was found that the polyphenolic substances of jerusalem artichoke tubers have a great influence on the technological properties of raw materials, the quality and nutritional value of the finished product. It was found that the enzymatic process of oxidative transformation of polyphenols occurs as much as possible in the first 5-10 minutes